2014
DOI: 10.5897/ajpp2013.3520
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an anti-microbial biflavonoid from the chloroform-soluble fraction of methanolic root extract of Ochna schweinfurthiana (Ochnaceae)

Abstract: The chromatographic investigation of the chloroform soluble fraction of methanolic root extract of Ochna schweinfurthiana using a combination of silica and sephadex LH-20 led to the isolation of trimethoxy derivative of lophirone A. The structure of this new compound was determined using both 1 and 2D nuclear magnetic resonance (NMR). The antimicrobial activity of the isolated compound was also investigated using agar diffusion and broth dilution techniques. Clinical isolates obtained from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Plant extracts were prepared according to the method described by Ndjonka et al [ 17 ] and Abdullahi et al [ 18 ]. Briefly, 50 g of powdered plant organs were extracted in 500 mL of ethanol-distilled water (70:30) and MeOH-CH 2 Cl 2 (50:50 v /v) for 48 h at room temperature, centrifuged (3500×g, 10 min) and filtered over filter papers No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant extracts were prepared according to the method described by Ndjonka et al [ 17 ] and Abdullahi et al [ 18 ]. Briefly, 50 g of powdered plant organs were extracted in 500 mL of ethanol-distilled water (70:30) and MeOH-CH 2 Cl 2 (50:50 v /v) for 48 h at room temperature, centrifuged (3500×g, 10 min) and filtered over filter papers No.…”
Section: Methodsmentioning
confidence: 99%
“…For fractionation, dried powder of leaves (1.5 kg) and root bark (2 kg) were macerated with 4 L of MeOH-CH 2 Cl 2 (50:50 v /v) for 48 h then filtered with wattman paper No. 1 [ 18 ]. The organic solvents were concentrated under reduced pressure at 40 °C, using rotary evaporator (Buchi Rotavapor R-210, Germany) to yield crude extracts of leaves (5.24%) and root bark (3.94%) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After which the plates were observed for colony growth, the MBC/MFC was recorded as the lowest concentration of compounds showing no bacterial/fungal growth. 16…”
Section: Minimum Bactericidal/fungicidal Concentration (Mbc/mfc)mentioning
confidence: 99%
“…Ochna schweinfurthiana F. Hoffm is a tropical small tree that measures upto 4 metres and belongs to the Ochnaceae family. It is used by the population of North Cameroon to treat different metabolic diseases involving mechanisms of oxidation or inflammation such as rubella, burns, stomach ache, and multiple sclerosis [11]. Several studies revealed that the Ochnaceae family is a rich source of complex metabolites such as flavonoids, chalcones, steroids, terpenoids, and alkaloids [1214].…”
Section: Introductionmentioning
confidence: 99%